Design And Development Of Microcontroller Based Localised Air Heater - M.Z, Hilwa; Woon Loong, Fu; Ismail, Nurhidayah (2012)
Although Malaysia is an equatorial country that has a tropical climate, it still has several places that has relative low ambient temperature due to the high altitude. For Cameron Highlands, the air temperature is ranged from 14.6°C to 23.3°C along the year. Humans may feel uncomfortable or unwell since the thermal comfort zone of human body ranges from 20°C to 27°C. Hence, an air heating system needs to be developed in order to solve this problem. This paper discussed the development of an air heating system that can heat up the room automatically when the temperature drops to certain value. This system is designed for a low cost but high performance. The microcontroller is used to provide control mechanism when the sensors detected a temperature drop. Fans and heating elements provide the air flow and heat.